The Construction of the Heroism of Mariana de Jesús: National Identity and Collective Suffering - Gutiérrez Chong, Natividad (2010)
This article addresses three interrelated themes in the study of national identity: collective suffering, the aggression of nature related to earthquakes and the construction of heroism based on a feminine icon: Mariana de Jesús. To explain the novelty of these themes, we resort to a methodological proposal that combines three types of nationalism and a typology of women’s roles in nationalisms. With these resources, we demonstrate that the rise of the myth of this heroine is pre-nationalist but its massive socialization is framed in the construction of the nation by the oligarchy and the church during the 20th century. The article is based on primary documentary sources.